Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3026015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Population and "Structural" Biases on Social Media-based Algorithms

Abstract: Much research has shown that social media platforms have substantial population biases. However, very little is known about how these population biases affect the many algorithms that rely on social media data. Focusing on the case study of geolocation inference algorithms and their performance across the urban-rural spectrum, we establish that these algorithms exhibit significantly worse performance for underrepresented populations (i.e. rural users). We further establish that this finding is robust across bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Edelman and Luca also found non-Black hosts were able to charge approximately 12% more than Black hosts, holding location, rental characteristics, and quality constant [27]. Colley et al found Pokémon GO advantaged urban, white, non-Hispanic populations, for example, potentially attracting more tourist commerce to their neighborhoods [15], and Johnson et al found that geolocation inference algorithms exhibited substantially worse performance for underrepresented populations, i.e., rural users [47].…”
Section: Background Algorithmic Fairnessmentioning
confidence: 99%
“…Edelman and Luca also found non-Black hosts were able to charge approximately 12% more than Black hosts, holding location, rental characteristics, and quality constant [27]. Colley et al found Pokémon GO advantaged urban, white, non-Hispanic populations, for example, potentially attracting more tourist commerce to their neighborhoods [15], and Johnson et al found that geolocation inference algorithms exhibited substantially worse performance for underrepresented populations, i.e., rural users [47].…”
Section: Background Algorithmic Fairnessmentioning
confidence: 99%
“…In the accessibility literature, design choices have repeatedly been shown to discriminate against disabled users [16]. Systemic technological biases against rural users and users of lower socioeconomic status have also been shown in the context of social media algorithms [7] and the sharing economy [13]. The consequences of biased design are particularly severe for vulnerable and marginalized populations.…”
Section: Discussionmentioning
confidence: 99%
“…This effect influences the design of geolocation inference algorithms, which have been shown to exhibit significantly worse performance for underrepresented populations (i.e. rural users), even when overcorrecting for populations biases [26].…”
Section: Media Bias In Communication and Social Mediamentioning
confidence: 99%